Dural Puncture Epidural Analgesia for Labor: A Randomized Comparison Between 25 and 27 G Pencil Point Spinal Needles. Issue 2 (June 2020) - Contreras, F.; Morales, J.; Bravo, D.; Layera, S.; Jara, A.; Riaño, C.; Pizarro, R.; De La Fuente, N.; Aliste, J.; Finlayson, R.; Tran, D.
Abstract : ( Reg Anesth Pain Med . 2019;44:750–753) Dural puncture epidural analgesia (DPEA) is the technique of passing a small gauge spinal needle through a Tuohy needle located in the epidural space to create a hole in the dura. Following the creation of this hole, the spinal needle is withdrawn without injection of intrathecal medication, and a catheter is placed within the epidural space. DPEA performed with 25 and 26 G pencil point spinal needles have demonstrated shorter onset time and improved sacral blockade compared with the traditional epidural technique; however, a large prospective trial demonstrated an increased incidence of postdural puncture headache (PDPH) after using a 25 G compared with a 27 G needle. Thus, the goal of this study was to compare DPEA using 25 and 27 G pencil point spinal needles. The primary outcome was onset time, which was defined as the temporal interval required after catheter placement to obtain a pain score ⩽1 using a 0 to 10 Numeric Rating Scale.